WALL CERAMIC MATERIALS BASED ON TECHNOGENIC RAW MATERIALS OF COAL SERIES - A. S. Gaishun; E. S. Gaishun; E. V. Kovaleristova; K. S. Yavruyan (Вестник Дагестанского государственного технического университета: Технические науки)
Objectives. The paper discusses the feasibility of using the technogenic raw materials of the coal series in the production of highly efficient wall ceramics. The interest in the man-made raw materials of the coal series (sludge, screenings and cake) as the raw materials used in the manufacture of ceramic products has now greatly increased. The reason for this was the reduction of the base of high-quality clay raw materials, the appreciation of its use in the production of wall ceramics, a large amount of accumulated reserves of various rocks of coal-based man-made raw materials.Method. The research used the following composition of the raw mix: 70% of technogenic raw materials of the coal series (screenings) and 30% of the clay raw materials. The determination of the physicomechanical properties of the samples was carried out according to GOST 530-2012. Coal dumps are fine- grained products, the solid part of which contains a significant amount of coal.Result. The technological parameters of obtaining wall ceramic products based on coal slimes are determined. Studied the main physico-technical characteristics of the materials obtained. Phase transformations occurring during the burning and patterns of the formation of the structure of the shard were studied. The feasibility of the production of highly efficient ceramic products with low thermal conductivity and density based on technogenic raw materials of the coal series using the technology of compression molding is shown.Conclusion. The results of theoretical studies are confirmed by practical data, which consist in the fact that in raw mixtures containing technogenic raw materials of coal series, a sharp increase in strength, taking into account the complete burning of carbon, occurs at temperatures of 1000-1060 ° C. The changes introduced during the production of products using this method will help achieve a significant energy saving of gas and optimization of the firing mode.